2011
DOI: 10.2320/matertrans.h-m2011802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Martensitizing Temperature on Creep Strength of Modified 9Cr Steel

Abstract: A modified 9Cr-1Mo steel was cooled to a temperature between the M s point and room temperature from the normalizing temperature and then directly heated to the tempering temperature. It was found that the time to rupture at 650 and 700 C of the steel heat-treated by the new heat treatment increased 2-3 times longer than that of the steel conventionally normalized and tempered. The microstructure of the improved steel was tempered martensite and the size of martensite blocks was larger than for the conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, it is reported that the retained austenite would be helpful to the creep resistance of weld deposit because of the transformation to un-tempered martensite even after the adequate heat treatment [48] . Tamura et al [49] suggested that the untransformed austenite would evolve into a new microstructure during subsequent tempering, which was related to the peaks in hardness and time to rupture of modified 9 wt% Cr steel. To obtain certain amount of retained austenite in 9 wt% Cr steels, after the austenization treatment, the steels can be cooled to a temperature between the martensite start temperature (M s ) and finish temperature (M f ) for different time [50] .…”
Section: Retained Austenitementioning
confidence: 98%
“…However, it is reported that the retained austenite would be helpful to the creep resistance of weld deposit because of the transformation to un-tempered martensite even after the adequate heat treatment [48] . Tamura et al [49] suggested that the untransformed austenite would evolve into a new microstructure during subsequent tempering, which was related to the peaks in hardness and time to rupture of modified 9 wt% Cr steel. To obtain certain amount of retained austenite in 9 wt% Cr steels, after the austenization treatment, the steels can be cooled to a temperature between the martensite start temperature (M s ) and finish temperature (M f ) for different time [50] .…”
Section: Retained Austenitementioning
confidence: 98%
“…On the other hand, the innovative thermal treatment (TT2) to be applied on COIN2 increases the normalizing temperature approximately 100 °C, reduces the tempering temperature 15 °C, and adds a martensitization step (intermediate step between normalizing and tempering where the steel after normalizing is cooled down to a temperature below Ms and above RT to retain a certain percentage of austenite). Such a novel processing route pursues an enhanced control of the microstructure [29].…”
Section: Thermal Treatments Investigationmentioning
confidence: 99%
“…With TT2, other options may arise. Based on literature [29], in the martensitization, the transformation of austenite into martensite is interrupted at certain temperatures (MT10 or MT30) at which some austenite (10% or 30%) can be retained and stabilized with the martensite formed. Afterwards, in tempering, that austenite may transform into ferrite and carbides/carbonitrides, and martensite is tempered.…”
Section: Thermal Treatments Investigationmentioning
confidence: 99%
See 2 more Smart Citations